2017
DOI: 10.1152/japplphysiol.00687.2016
|View full text |Cite
|
Sign up to set email alerts
|

Ocular changes over 60 min in supine and prone postures

Abstract: Some astronauts are returning from long-duration spaceflight with structural ocular and visual changes. We investigated both the transient and sustained effects of changes in the direction of the gravity vector acting on the eye using changes in body posture. Intraocular pressure (IOP; measured by Perkins tonometer), ocular geometry (axial length, corneal thickness, and aqueous depth-noncontact biometer), and the choroid (volume and subfoveal thickness optical coherence tomography) were measured in 10 subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 42 publications
5
18
0
Order By: Relevance
“…Studies have shown that changes in the gravitational environment can have pronounced transient and sustained effects on the eye 24 . Microgravity-induced vision changes may result from the interaction of multiple physiological factors, including changes in IOP, fluid shifts, ocular geometry and cardiovascular alterations 2527 . Similarly, increases in IOP have been documented in ground-based models of spaceflight, such as head-down tilt 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that changes in the gravitational environment can have pronounced transient and sustained effects on the eye 24 . Microgravity-induced vision changes may result from the interaction of multiple physiological factors, including changes in IOP, fluid shifts, ocular geometry and cardiovascular alterations 2527 . Similarly, increases in IOP have been documented in ground-based models of spaceflight, such as head-down tilt 28 .…”
Section: Discussionmentioning
confidence: 99%
“…lack of normal circadian variation in ICP (Lawley et al 2017), or upward brain shift (Shinojima et al 2018) other than pathologically elevated ICP. It is also possible that there are other features of long-duration spaceflight that are more specific to hydrostatic gradients within eye itself that could be responsible, independently of ICP as hypothesized by Buckey et al (Anderson et al 2017). It should be emphasized that both astronauts with SANS signs showed increases in mean MCAv and heart rate and decreases in haemoglobin concentration after spaceflight, similar to the changes of the group averages of the 11 astronauts.…”
Section: Two Astronauts With Optic Disc Oedema and Choroidal Foldsmentioning
confidence: 54%
“…(Anderson et al . 2017). It should be emphasized that both astronauts with SANS signs showed increases in mean MCAv and heart rate and decreases in haemoglobin concentration after spaceflight, similar to the changes of the group averages of the 11 astronauts.…”
Section: Discussionmentioning
confidence: 99%
“…On the testing day, subjects experienced each of the four experimental conditions in a randomized order: 1) standing, 2) supine, 3) AGEC, and 4) AG2G. In each condition, participants first acclimatized for 10 min in the posture before taking measurements, to allow the cardiovascular system and IOP to equilibrate (1). Subjects remained stationary, feet shoulder width apart, hands at their side.…”
Section: Subjectsmentioning
confidence: 99%
“…These short-term effects may not be indicative of ocular status once the eye has reached steady state under AG exposure. A study by Anderson et al (1) found IOP has a time constant of 5.3 min, reaching steady-state pressure in~10 min when going from the seated to the prone position. Furthermore, the Chung study used long-radius centrifugation, whereas current investigations for AG to mitigate SANS have been proposed as short-radius centrifugation, where head-to-toe hydrostatic gradients are larger (14,21).…”
Section: Introductionmentioning
confidence: 99%